Settler colonialism, Indigenous cultures, and the promotional landscape of tourism in Ontario, Canada's 'near North'. Issue 3 (4th May 2019) - Grimwood, Bryan S. R.; Muldoon, Meghan L.; Stevens, Zachary M.
ABSTRACT: Settler colonialism relies upon a logic of elimination that strives to dissolve Indigenous culture and title to ancestral lands. In Canada, settler colonialism has steered not only oppressive state policy directions, but also settler narratives that essentialize and displace Indigenous Peoples and cultural connections to land. Tourism is an especially potent social force through which such settler stories can be perpetuated and resisted. The purpose of this paper is to analyze how Indigenous culture is portrayed in the tourism promotional landscape of Ontario's 'near north', a rural leisure landscape for nature enthusiasts and second-home owners. While Anishinaabeg and Haudenosaunee First Nations have inhabited this area for generations, their cultural presence is often marginalized in development discourses, both historical and contemporary. Our study draws upon critical discourse analysis of websites produced by stakeholders associated with three case study sites – a Provincial Park, an annual cranberry Festival, and a major casino operation – to understand both the limits and opportunities of tourism in relation to maintaining and revitalizing Indigenous culture. In so doing, our paper contributes to critiques of settler colonial power relations and how these infiltrate tourism, and identifies pathways for disrupting the erasure of Indigenous cultures in tourism.